CPITN: time and cost estimates for periodontal prevention and treatment procedures. - Dini, E. L.; Castellanos, R. A. (My University, 1995)
The aim of this study was to estimate the necessary time and cost for periodontal prevention and treatment in a working population from sugar and alcohol refineries in Araraquara, SP, Brazil. A stratified sample of 528 employees aged 18-64 from administrative, industrial and agricultural staffs was examined by one examiner, previously trained, according to the community periodontal index of treatment needs (CPITN). The time required for procedures and the cost was extrapolated to the total worker population. The results showed that the estimated time required for periodontal prevention/treatment was 4527 hours. Of this time, 1783 hours were required for oral hygiene instruction, 2531 for scaling, 151 for surgery and 62 for maintenance. The cost would be US $17,655 for hiring a dentist for 8 hours/day to provide oral hygiene instruction, scaling, surgery and maintenance. However, the cost would be US $9,028 for hiring a dentist for 4 hours/day to provide surgery and maintenance and a dental hygienist for 8 hours/day to provide scaling and oral hygiene instruction. Taking into account epidemiologic, technical and economic aspects, the decision relating to manpower should be this second option.
Keywords: adolescent; adult; Brazil; cost; dental assistant; economics; health care planning; health service; human; manpower; middle aged; patient education; periodontal disease; periodontics; preventive dentistry; statistics; time; Adolescent; Adult; Costs and Cost Analysis; Dental Hygienists; Dental Prophylaxis; Health Planning; Health Services Needs and Demand; Humans; Middle Aged; Patient Education; Periodontal Diseases; Periodontal Index; Periodontics; Time Factors